Engineering Education in the 21st Century: Towards a New Educational Paradigm - HANNI, Kaoutar (Revue Internationale du Chercheur, 2021)
Today, various mobile technologies have profoundly affected many aspects of human life including our way of living, our habits, and the way we work and think, etc. With advances in communication technologies and electronic devices, learners now are capable of accessing and managing information from their smart phones or other technological gadgets. In fact, educational systems have already started implementing ICT into their curriculum and pedagogy responding to the pressures of the digital age and thus, preparing the citizens for the information society. In addition to guaranteeing efficient learning and engaging learners in constructing knowledge, technology offers further chances for success. Besides, by implementing more instructional high-tech tools such as online courses, Interactive White Boards, digital libraries, etc. this may revolutionize the engineering practices, and increase the whole learning experience for the learners of the 21st century. In this regard, this research study investigates the issue of teaching and learning engineering education in the Information age shedding the light on the modern learning practices resulting from the ongoing growth process of information technologies.